Integration of Islamic Ethics and Principles in Modern Financial Institutions in Nigeria: Challenges and Opportunities - Isiaka Adewale Lawal; Azeez Oyedeji (PT. Student Rihlah Indonesia, 2026)
The modern financial system has evolved significantly over time, alongside advancements in various parts of the world. This study attempts to examine the integration of Islamic ethics and principles in modern financial institutions in Nigeria with a focus on Sharī'ah-compliant practices, risk sharing, and social responsibility. It also discusses the adoption and implementation of Islamic ethics such as iḥsān, ‘adl, and ’amānah in financial decision making, including enhanced financial stability, social justice, and sustainability, to explore the extent to which the adoption could benefit the financial institutions and society. The findings from this study revealed the importance of incorporating Islamic ethics in the modern financial system so that its innovations can also improve and benefit society.